(untitled) (Scientific journal of the Fergana State University, 2025)
The article aims to elucidate the concepts and characteristics of thinking, analytical thinking, independent healthy worldview, and philosophical analytical reasoning, as well as the essence of state policies regarding youth. Furthermore, it analytically discusses the necessity of developing thinking and forming an independent healthy worldview among members of society, particularly students, in light of various ideological threats, manipulative programs, and the struggle for human consciousness that have intensified in the 21st century.